Social and psychological characteristic bullying in nonformal teenage groups - Kifa, Anastasia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The progressive alienation, increased anxiety, spiritual desolation modern teenagers leads young people to cynicism, excessive violence and aggression. Quite often raised questions bullying in the school environment, every year the number of scientific publications is growing, but the question bullying in non-formal and informal groups are poorly understood.Non-formal groups of teenagers can affect teenage both positively and negatively. It is in these groups of teenagers have the opportunity to prove themselves and gain prestige. Quite often, teenagers who for some reason have not established formal positive relationships with other teenagers in the school is very successful in terms of social relations in non-formal teenage groups.Bullying problem can not be solved locally only in the school, needed a completely new and comprehensive approach to the problem of display bullying in various teen groups.
Keywords: bullying; informal groups non-formal group; formal group; teen group